Internal Evaluation Of Medical Laboratory Sciences Department Of Allied Health Sciences School, Tehran University Of Medical Sciences(2010) - Nasrin Dashti; Nahid Einollahi; Mitra Zare Bavani; Sakineh Abbasi (پیاورد سلامت, 2012)
Background and Aim: Internal Evaluation is a process of providing evaluative-descriptive information based on the value and significance of educational objectives, operations and results to direct decisions, responses, information and research processes. Materials and Methods: In this research, studying the opinions of faculty members, students, and graduates, the educational system of Medical Laboratory Sciences Department at Tehran University of Medical Sciences (TUMS) was evaluated in the year 2010. The aim the study was to remodel and adjust the educational system with the society's needs and to promote the educational quality. The employed method was a cross-sectional, descriptive one and consisted of 10 procedural steps in eight sections dealing with the evaluated factors such as faculty members and students, and the satisfaction expressed by students.